Pengaruh Supervisi Akademik Kepala Sekolah, Kepuasan Kerja dan Motivasi Kerja terhadap Kinerja Guru Sekolah Dasar di Kecamatan Ujungbatu - Franciscus, Finder; Caska, Caska; Azhar, Azhar (Jurnal Pendidikan Tambusai, 2021)
This study aims to examine the effect of principal's academic supervision, job satisfaction, and work motivation on teacher performance at the Ujungbatu District Elementary School. This research method is quantitative by using a questionnaire as a data collection tool. The population in this study was 337 teachers, while the sample in this study was 158 teachers from 18 public elementary schools in Ujungbatu District using random sampling technique. The results showed that 1) there was a significant positive effect of principal supervision on teacher performance as indicated by the regression equation = 22.025 + 0.673X1, with a contribution of 19%. 2) there is a significant positive effect of job satisfaction on teacher performance with the regression equation = 22.063 + 0.629X2, with a contribution of 19%. 3) there is a significant positive effect of work motivation (X3) on teacher performance (Y) as indicated by the regression equation = 14.832 + 0.793X3 with a contribution of 7.9%. 4) there is a significant positive effect of the principal's academic supervision (X1), job satisfaction (X2), and work motivation (X3) together on teacher performance (Y) as indicated by the regression equation = 34.871 + 0.363X1 + 0.381 X2+ 0.609X3 with an influence contribution of 27.8%.